Investigation on the Removal of Carbon Dioxide Exhausted from Industrial Units in a Lab-Scale Fluidized Bed Reactor - Puriya Mohamad Gholy Nejad; Mohammad Sadegh Hatamipour (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
In this study, CO2 removal efficiency from flue gas was investigated in a fluidized bed reactor under semi-dry conditions. A lab-scale fluidized bed reactor, filled with inert glass beads, was used to investigate the effect of operating parameters on the CO2 removal efficiency using calcium hydroxide slurry as the absorbent. The Taguchi design method was used to design the experiments. The maximum inlet concentration of CO2 was 3 vol%. The most important factors were the reaction surface area, inlet gas velocity, inlet CO2 concentration, absorbent solution flow rate, inlet gas temperature and calcium hydroxide slurry concentration. The experimental results indicated that the CO2 removal efficiency increased when increasing the effective surface area of the reaction. Moreover, the removal efficiency increased by decreasing the input gas flow rate and inlet CO2 concentration. By performing experiments under optimum conditions, the maximum obtained CO2 removal efficiency was 79%. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).